Search engine optimization algorithms for page ranking: comparative study - Ullah, Arif; Mohd Nawi, Nazri; Sutoyo, Edi; Shazad, Asim; Khan, Sundas Naqeeb; Aamir, Muhammad (Penerbit UTHM, 2018)
:No doubt that every second in our daily routine, the number of visitors that connect to the internet increase day by day due to the fast growing of World Wide Web. Until this day there are more than 11.3 billion web pages in the World Wide Web. In the modern era of technology and advance computation, world page ranking is becoming a common feature of modern retrieval system. However, many of us did not realise that any query in search engine will display both relevant and irrelevant data that can cause overhead to the search engine and will affect the page ranking process. Therefore, a new optimization technique to improve the existing search engine optimization in increasing the page ranking is needed. This paper presents a review and comparative study of different existing page ranking algorithms for search engine optimization. This paper also explores some improvements that are needed to overcome the current problem in this field by testing on some real case data. The simulation result’s analysis clearly shows that there is a need for new optimization technique which can reduce the complexity and user overhead by displaying only related data which will reduce over heading in search engine.